Pengaruh Rasio Profitabilitas, Rasio Solvabilitas Dan Rasio Pasar Terhadap Harga Saham Pada Perusahaan Sektor Transportasi Dan Logistik Yang Tercatat Di Bursa Efek Indonesia Periode 2019-2023 - Sarrah Nur Rizkya Febrianti (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to examine the effect of profitability ratio, solvency, and market ratio on stock prices in the transportation and logistics sector on the Indonesia Stock Exchange for the period 2019-2023. The method used is quantitative descriptive with secondary data from the official website of the Indonesia Stock Exchange. The sample was selected using the purposive sampling method, involving 18 out of 37 companies. The analysis was carried out using descriptive tests, regression, and normality tests, multicollinearity, heteroscedasticity, autocorrelation, t-test, f-test, and coefficient of determination. The results of the study indicate that simultaneously and partially, profitability, solvency, and market ratio have a significant effect on stock prices. The analysis technique used is linear regression analysis with the SPSS version 25 application program.